Targeted 64Cu‐labeled gold nanoparticles for dual imaging with positron emission tomography and optical imaging. (28th May 2019) - Pretze, Marc; van der Meulen, Nick P.; Wängler, Carmen; Schibli, Roger; Wängler, Björn
Abstract : Gold nanoparticles (AuNPs) have been used for many years in cancer treatment mainly for brachytherapy, but in the last 15 years, the focus has shifted to the development of ultrasmall target‐specific AuNPs with homogeneous size and, ultimately, tailored shapes for use in various imaging modalities such as computed tomography (CT), Raman, or photoacoustic imaging. Here, we report on the development of tumor‐specific AuNPs as diagnostic tools intended for the dual detection of prostate cancer via optical imaging (OI) and positron emission tomography (PET). The AuNPs were decorated with a near‐infrared dye and NODAGA chelator for complexation with radiometals. Radiolabeling with 64 Cu was performed either indirect by complexation with NODAGA‐AuNPs or by direct reduction of [ 64 Cu]Cu(0) onto the surface of the AuNPs. Both methods yielded stable 64 Cu‐AuNPs with radiochemical yield more than 95% confirmed by HPLC. 64 Cu‐AuNPs were evaluated in a dual‐imaging setting in vitro and in vivo and exhibited favorable diagnostic properties concerning detection, biodistribution, and clearance. Furthermore, the first therapeutic properties of the 64 Cu‐AuNPs were evaluated in vitro concerning acute and long‐term toxicity, indicating that these 64 Cu‐AuNPs could be used in therapeutic concepts in the future. Abstract : Gold nanoparticles (AuNPs) were synthesized for targeted imaging of prostate cancer with optical imaging and positron emission tomography. Their stability and therapeutic properties were evaluated in vitro, and their pharmacokinetics and biodistribution were evaluated in vivo. The AuNPs were tested for multimodal imaging.